Yüksək dəqiqli yuvaların pardaqlanmasında rejim parametrlərinin idarə olunması hesabına prosesin optimallaşdırılması - Talıbov, Təvəkkül; Abdullayev, Məmməd (My University, 2024)
High-precision slot polishing is carried out in order to optimize the process, achieve the best possible results, and increase the efficiency of the work process.
Process optimization through mode parameter control in high-precision slot polishing
Keywords: Slot polishing; Polishing parameters